Social Exclusion of Homeless and its Formation - Kocai, Elena (Sociologija. Mintis ir veiksmas, 2008)
The paper analyzes the process of homeless social exclusion, its stages, also main levels and factors of exclusion. In the article it is maintained that not only heavy economic situation (destitution of home, unemployment, low incomes) of the homeless, intermitted social links and insufficiently effective social policy of the state condition their exclusion, but also individual spiritual and mental features of the homeless themselves that determine their stigmatization and ostracism. Social exclusion of homeless is a double-sided process: firstly, it is predetermined by the peculiarities and conduct of the individual, secondly – by the social environment where he lives.